Pemberian Edukasi Kepada Pelajar di Kabupaten Lamandau Mengenai Smart Agriculture - Roni Ismoyojati; Devi Devi (BERNAS: Jurnal Pengabdian Kepada Masyarakat, 2024)
The world's increasing food needs due to the increase in population have caused humans to increasingly innovate to increase plant productivity. Smart Agriculture is the current answer that can be utilized and optimized to increase the productivity and sustainability of agricultural systems. This PkM activity was carried out online involving students in Lamandau Regency as activity participants. The aim of this PkM activity is to provide additional information and insight for students in Lamandau Regency regarding Smart Agriculture. The method used is lecture and activity stages consisting of, 1) Preparation Stage; 2) Implementation Phase and 3) Evaluation Phase. As a result of this PkM activity, understanding of Smart Agriculture among students has increased and motivated students to innovate and deepen knowledge related to Smart Agriculture.